2022
DOI: 10.3390/antibiotics11010087
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antibiotics on Planktonic Cells and Biofilm Formation Ability of Collected Arcobacter-like Strains and Strains Isolated within the Czech Republic

Abstract: The purpose of this study was to test the in vitro effects of ampicillin, ciprofloxacin, clindamycin, erythromycin, gentamicin, and tetracycline on planktonic cells of Arcobacter-like microorganisms and on their biofilm formation ability. The minimum inhibitory concentrations (MICs) were determined by the microdilution method. Further, biofilm formation ability in the presence of various concentrations of antibiotics was evaluated by a modified Christensen method. Most of the 60 strains exhibited high suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This virulence-enhancing property of some microorganisms can play a significant role in disease pathogenesis. Infections caused by biofilms are typically chronic in nature, as the bacteria in the biofilm structure are resistant to the immune system response and to many antimicrobials [ 20 , 48 ]. The ability to form a biofilm was monitored in 85 strains isolated from smoothie drink samples by using the Christensen method with microtiter plates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This virulence-enhancing property of some microorganisms can play a significant role in disease pathogenesis. Infections caused by biofilms are typically chronic in nature, as the bacteria in the biofilm structure are resistant to the immune system response and to many antimicrobials [ 20 , 48 ]. The ability to form a biofilm was monitored in 85 strains isolated from smoothie drink samples by using the Christensen method with microtiter plates.…”
Section: Resultsmentioning
confidence: 99%
“…There were 8 wells in each experiment, and the experiments were independently repeated 3 times. The level of biofilm formation was categorized, according to a previously described classification system [ 20 , 21 ], as non-adherent (OD ≤ OD C ) or biofilm-forming strains (OD > OD C ), where OD C ( cut-off OD) is defined as three standard deviations above the mean OD of the negative control (blank value).. The measured and calculated OD/OD C (0.111/0.120) values were the same for all measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Šilha et al, (2021) suggested that Arcobacter-like species tend to prefer microaerophilic environments but are capable of forming biofilms in both microaerobic and aerobic conditions [57]. However, other studies have shown that aerobic conditions could favour biofilm formation for most of the studied strains, showing that a strain-dependent response could be responsible for the variability of the results [50,[57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 98%
“…The increased resistance of bacteria to antimicrobials is a matter of great concern worldwide; therefore, monitoring the antimicrobial resistance of microorganisms is especially important [ 24 ]. Previous studies confirm that many natural matrices and extracts have antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…There were 8 wells in each experiment, and the experiments were independently repeated 3 times. The level of biofilm formation of the Arcobacter -like strains was categorized, according to a previously described classification system [ 24 ], as non-adherent (OD ≤ OD C ) or biofilm-forming strains (OD > OD C ), where OD C ( cut-off OD) is defined as three standard deviations above the mean OD of the negative control (blank value). The measured and calculated OD/OD C (0.111/0.120) values were the same for all measurements.…”
Section: Methodsmentioning
confidence: 99%